Design and Physical Characterization of a Synchronous Multivalve Aortic Valve Culture System - Durst, Christopher A. (Ann Biomed Eng, 2009)
For many tissues, cyclic mechanical stimulation is considered necessary to maintain the normal morphology in vitro. The aim of this study was to design and evaluate a simple bioreactor system capable of medium-term (more than 2 weeks) culture of native and engineered aortic valves. The system consists of three pistons in separate cylindrical chambers that are simultaneously driven through the culture medium by a crank and cam assembly. The faces of these pistons have unidirectional valves mounted in opposing orientations that permit flow from one side of the face to the other. A custom designed stent was employed to secure either native or engineered trileaflet valves to the pistons. Computational fluid dynamics and finite element modeling was used to assist selection of materials and components in the system. Finally, sterility testing using base culture medium was performed to verify the ability of the system to retain sterile conditions. The current design permits the cyclic opening and closing of three aortic valves, however this device can be modified to accommodate up to 12 valves simultaneously. This new bioreactor system has applications not only for development of tissue-engineered valves, but for also studying disease models in the aortic valve.